Analisis Minat Belajar Siswa SD Pada Pembelajaran IPA Menggunakan Media Lagu Anak - Salma Azkiya Ainurruhama; Arsyi Rizqia Amalia; Irna Khaleda Nurmeta (JURNAL PENA EDUKASI, 2024)
Abstract: This study aims to analyze students' interest in learning in the Natural Sciences learning process using children's songs in elementary schools. The research method used is qualitative descriptive, with data collection techniques through reviewing the Natural Sciences class IV teaching module (documentation), observing the Natural Sciences learning process using children's songs, and interviewing class teachers and students in grade IV. The study's results indicate that children's songs can increase students' interest in learning science, according to the indicators the author has observed. Students become more enthusiastic, active, and interested and show attention during the learning process; children's songs also help students to understand the material being taught more efficiently, and students also participate during the learning process by singing the songs provided. This study concludes that using children's songs in science learning in elementary schools positively impacts students' interest in learning.Keywords: childrenâ€™s song media; interest to learn; learning process; natural science.Â Abstrak: Penelitian ini bertujuan untuk menganalisis minat belajar siswa pada proses pembelajaran Ilmu Pengetahuan Alam (IPA) menggunakan media lagu anak di sekolah dasar. Metode penelitian yang digunakan adalah kualitatif deskriftif, dengan teknik pengumpulan data melalui telaah modul ajar IPAS kelas IV (dokumentasi), observasi proses pembelajaran IPA menggunakan media lagu anak, dan wawancara kepada guru kelas dan siswa kelas IV. Hasil penelitian menunjukkan bahwa penggunaan media lagu anak dapat meningkatkan minat belajar siswa dalam pembelajaran IPA sesuai dengan indikator yang telah penulis amati. Siswa menjadi lebih semangat, aktif, tertarik serta menunjukkan perhatian pada saat proses pembelajaran berlangsung, media lagu anak juga membantu peserta didik untuk lebih mudah memahami materi yang diajarkan, para peserta didik juga ikut berpartisipasi pada saat proses pembelajaran berlangsung dengan menyanyikan lagu yang disediakan. Penelitian ini menyimpulkan bahwa penggunaan media lagu anak pada pembelajaran IPA di sekolah dasar memiliki dampak yang positif terhadap minat belajar siswa.Kata kunci: Ilmu Pengetahuan Alam; media lagu; anak minat belajar; proses pembelajaran.